Analogous Labneh processing fortified with protein by controlled structure method to study its chemical, microbial, sensory proprieties (Damascus University Journal of agriculture sciences, 2021)
33 samples of analogous Labneh were produced from milk powder and fortified with different percent of  sodium caseins, vegetable butter and Gelatin to total solid  of  25% without  whey separation to study sensory   proprieties , chemical structures, microbial load  and storage  condition of Labneh in 5, 10 and 15 Cº for 20 days. Results reveal that they were significant differences in all treatments of analogous  Labneh samples for protein, ashes, and total solid and no significant differences for lactic acid and pH .  M6 sample showed by sensory evaluation high acceptance for low acid ,  good flavor and  firm texture with less whey separation. Also, the results of  microbial contamination showed  that they were  no coliform,  yeast and fungi in all tested samples and therefore, M6 sample could be stored under 5 Cº to 20 days with minor differences in lactic acid production while  10 and 15 Cº  storage showed  increase in lactic acid and decrease in pH  for 10 and 15 days respectively.
Keywords: Analogous Labneh; Sodium caseins; Chemical structure; Microbial load; Sensory evaluation; Storage conditions